Block chain Technology Applications in the Hotel Industry: A Systematized State-of-Art Review and Evidence–Based Synthesis - Dr. Srinivasa Rao Bandaru, Dr. Sujatha Kamepalli, Dr. K. V. K. Kishore, Dr. Nannapaneni Chandrasekhrarao (International Journal of Control and Automation, 2020)
In the digital era, the role of technology in creating disruptions in both the production and service sectors is commendable. Today, Block chain technology (BCT) is a frontrunner in creating disruptions in most of the production and service sectors. Hoteliers are contemplating adopting BCT in their domain. The potential of evidence-based sensible insights of a domain can ignite and illuminate research practice and scope for further research. This paper provides systematized state-of-art review and evidence-based synthesis on applications of BCT to the hotel industry. The review provides extensive evidence-based information on applications of BCT in the hotel industry for the stakeholders for adoption and choice decisions. The findings disclose that majority of the chain hotels are eager about blockchain technology due to more business functions and collaborations. It is obvious that the hotel industry immediately needs to adopt BCT to meet guest customized expectations and enter into the personalization era/Industry 5.0.